An unholy alliance : the sacred and modern sports - Higgs, Robert J., 1932-2015.; Braswell, Michael (Macon, Ga. : Mercer University Press, 2004)
"An Unholy Alliance offers a dissenting view to the claim by a growing number of scholars that sports are a new religion. The last few years have seen a spate of books that might be classified by a genre called "Sports Apologetics, " that is, arguments defending or celebrating in one way or another the familiar and ongoing alliance in America between sports and religion." "In this book, Higgs and Braswell suggest that while sports may often be good things, they are not inherently divine. They do not focus on widespread abuse in sports as evidence for their counterargument. Rather, they question the use of mythological parallels from prehistory as justification for viewing sports as a religion."--Jacket.
Sports and Religion: Peanut Butter and Jelly or Oil and Water? -- What's in a Name? Working Definitions of Sports and Religion -- The Sacred and the Holy: Distinguishing the Indefinable -- Wisdom and Strength: Two Faces of the Holy -- The Religion of Sports and the Media: Marshall McLuhan among the Apologists -- The Cross in the Coliseum: Sacred Ground and Battle Ground -- Religion, Sports, and War: The Conflicted History of the Knight and the Shepherd -- The Religion of Sports and That Old-time Religion: In the Steps of Mircea Eliade -- Varieties of Mystical Experiences: Old and New -- The Holy and the "Flow": Ultimacy Versus Intimacy -- Ethics, Values, and Excellence: Testing the Spirits -- The Statue of Zeus and Creation of Adam Athletic Art as Sacred and Holy -- Humor and the Eternal Triangle: Mind, Sports, and Religion -- The High Seriousness of the Religion of Sports: A Return to Polytheism? -- : Apotheosis Versus Atonement -- Appendix 1: Religious Dichotomies -- Appendix 2: Textual Notes on Comparative Theology.
Includes bibliographical references and index.
Keywords: Sports -- Religious aspects